Retorika Tasybih dalam Hadis:Kajian Balaghah Shahih al-Bukhari - Nur Kholid; Badi'atus Solichah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study examines the use of tasybīh (simile) in Shahih al-Bukhārī as a rhetorical strategy to bridge abstract concepts of faith, deeds, and social values with tangible sensory experience. The method is a qualitative library research approach used to analyze the structural elements of tasybīh and tehir classifications. The findings reveal that Mufrad emphasizes singular traits such as solidarity and steadfastness, while tamṡīl presents complex situations such as spiritual hierarchy or the influence of companionship. These tasybīh serve the rhetorical function of affirmation, visualization, moral classification, and social warning. Beyond aesthetics, tasybīh in Shahih al-Bukhārī operates pedagogically by teaching moral distinctions through analogies, psychologically by evoking hope and fear through sensory imagery, socially by reinforcing solidarity and caution in relationships, and cosmically by connecting faith to symbols of light. Tasybīh in Shahih al-Bukhārī unites clarity of structure, stylistic variety, depth of meaning, and rhetorical power, transforming Islamic teaching into memorable and actionable guidance for life.